Close, bright, and boxy: the superluminous SN 2018hti. Issue 3 (17th March 2022) - Fiore, A; Benetti, S; Nicholl, M; Reguitti, A; Cappellaro, E; Campana, S; Bose, S; Paraskeva, E; Berger, E; Bravo, T M; Burke, J; Cai, Y-Z; et al.
ABSTRACT: SN 2018hti was a very nearby ( z = 0.0614) superluminous supernova with an exceedingly bright absolute magnitude of −21.7 mag in r band at maximum. The densely sampled pre-maximum light curves of SN 2018hti show a slow luminosity evolution and constrain the rise time to ∼50 rest-frame d. We fitted synthetic light curves to the photometry to infer the physical parameters of the explosion of SN 2018hti for both the magnetar and the CSM-interaction scenarios. We conclude that one of two mechanisms could be powering the luminosity of SN 2018hti; interaction with ∼10 M⊙ of circumstellar material or a magnetar with a magnetic field of B p ∼ 1.3 × 10 13 G, and initial period of P spin ∼ 1.8 ms. From the nebular spectrum modelling we infer that SN 2018hti likely results from the explosion of a 40 M_ progenitor star.